OPTIMIZATION OF PRODUCTIVE ZISWAF BY ZISWAF-BASED MINIMARKETS (CASE STUDY OF ALIF POINT MART MINIMARKET IN PADANG CITY) - Mahlil Bunaiya; Aufa Islami; Suud Sarim Karimullah (IAIN Batusangkar, 2022)
Abstract: The problem of social inequality today has not yet shown the maximum realization of the constitutional mandate and religious teachings. The description of the above conditions is a motivation for individual businesses to optimize the distribution of Ziswaf productively as implemented by the Alif Point Mart minimarket in Padang City. This new effort has become a study in maximizing the distribution of Ziswaf by Alif Point Mart in Padang City. This type of research is field research; the nature of this research is descriptive-analytic. They are collecting data using observation and interview methods. Then, it will be examined, classified, and analyzed after ordering it in processing the data. Then conclude using a qualitative descriptive research approach. The research results show that Alif Point Mart is a business in the retail and culinary sector whose operations are a combination of a minimarket and coffee business with the main principles in sharia business management. Alif Point Mart is a Ziswaf-based Mini Market, meaning that it is a business that has capital from shareholder funds or investments. The profits are allocated for alms, infaq, productive waqf in the form of business capital for people in need, and when the gains have reached the mandatory zakat, zakat will be issued 2.5%. The distribution of zakat is a program carried out every year to existing zakat institutions.